Revolution : interior design from 1950 - Plunkett, Drew (RIBA Publishing, 2016)
"The last half of the twentieth century saw the emergence, evolution and consolidation of a distinct interior design practice and profession. This book is invaluable for students and practitioners, providing a detailed specialist, contemporary historical analysis of their profession and is beautifully illustrated, with over 200 photos and images from the 1950s through to the present day."--Cover.